An Experimental Investigation and Parameter Optimization on Milling of Aluminum Alloy 6061 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, the experiments will be conducted to improve the surface finish quality ofaluminum alloy 6061 work piece by using carbide tips. The type is bull nose tip. A series ofexperiments will be done by varying the milling parameters spindle speed, feed rate and depthof cut. The spindle speeds are 3500rpm, 3000rpm and 2000rpm. The feed rates are200mm/min, 300mm/min and 400mm/min. Depth of cut is 0.2mm and 0.3mm and 0.4mm.Taguchi method is used to study the effect of process parameters and establish correlationamong the cutting speed, feed and depth of cut with respect to the major machinability factor,surface finish. Validations of the modeled equations are proved to be well within theagreement with the experimental data. Taguchi method is used to study the effect of processparameters and establish correlation among the cutting speed, feed and depth of cut withrespect to the major mach inability factor, surface finish. Validations of the modeledequations are proved to be well within the agreement with the experimental data.